Determination of crystal changes on sodium cobaltite (NaCo 2O4) by Reitveld analysis as a suitability function in thermoelectric materials - Muhammad Asri, Idris; Murizam, Darus; Norsuria, Mahmed (American Institute of Physics, 2010)
Link to publisher's homepage at http://scitation.aip.org/